2014
DOI: 10.18287/0134-2452-2014-38-2-281-286
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-spatial classification with k-means++ particional clustering

Abstract: A complex spectral–spatial classification scheme for hyperspectral images is proposed and explored. The key feature of method is using widespread and simple enough algorithms while having high precision. The method combines the results of a pixel wise support vector machine classification and the segmentation map obtained by partitional clustering using majority voting. The k-means++ clusterization algorithm is used for image clustering. Principal component analysis is used to prevent redundant processing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…When clustering incomplete data from congruent sources (e.g. hyperspectral information in Earth remote sensing), this complex can compete with traditional methods such as k-means [20].…”
Section: Resultsmentioning
confidence: 99%
“…When clustering incomplete data from congruent sources (e.g. hyperspectral information in Earth remote sensing), this complex can compete with traditional methods such as k-means [20].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we used this algorithm with the squared Euclidean distance measure. To initialize cluster centers we used the k-means++ algorithm [17,19]. It was shown that k-means++ algorithm achieves faster convergence to a lower local minimum than the base algorithm.…”
Section: Second and Third Principal Components Contrasted (B-d)mentioning
confidence: 99%
“…There are a growing number of papers that use both unsupervised segmentation and supervised classification techniques to build sophisticated classification methods with improved classification accuracy [5,6,19].…”
Section: Introductionmentioning
confidence: 99%
“…To form the hyperspectral cube [16], the sequence of spectrometer images should be processed. The hyperspectral image of the illuminated with white light graphic table was restored after the processing of the resulting images.…”
Section: Fig 6 the Spectral Image Of The Graphic Table Section Illmentioning
confidence: 99%